The New Times of Social Media Marketing in the B2B Framework - Lopes, João (2022)
Nowadays, we live in the age of Marketing 4.0. Historically, marketing has often depended on changing consumer habits and needs. Thus, it is necessary to understand the new habits and needs of the consumer to make companies more and more effective. Currently, social media marketing (SMM) is ubiquitous in organizations, and is seen as a tool to achieve strategic goals. Therefore, SMM is important for companies to adapt their approach to customer relationship management and advance new marketing competencies to enable customer satisfaction. To drive customer satisfaction and improve customer experience, managers are loading social media applications into their current customer relationship management (CRM) systems. This study seeks to understand the feasibility of implementing SMM in business to business (B2B) companies and how this affects CRM and customer knowledge management (CKM). For this study, data were collected from two Portuguese micro-companies. The methodology used was exploratory qualitative in nature through a multiple case study, wherein semi-structured interviews were applied. It was found that SMM cannot be used in the B2B companies under investigation because CRM needs are much more dependent on CKM than on the mass interactions and indirect communication with the customer that can potentially exist in SMM. In these companies, communication with the client can be adjusted on a case-by-case basis through SMM, without the need for mass communication with all clients. This paper provides implications for the management of micro-enterprises regarding social media marketing. It also contributes to the development of the literature on SMM, CRM and CKM.